United States : Publication of Financial Sector Assessment Program Documentation; Detailed Assessment of Observance of the Fixed Income Clearing Corporation; Government Securities Division's Observance of the CPSS-IOSCO Recommendations for Central Counterparties. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses key findings of the Detailed Assessment of Observance of the Fixed Income Clearing Corporation-Government Securities Division's Observance of the Committee on Payment and Settlement Systems/International Organization of Securities Commissions (CPSS-IOSCO) Recommendations for Central Counterparties (CCP) for the United States. The assessment recommends that a CCP should have a well-founded, transparent, and enforceable legal framework for each aspect of its activities in all relevant jurisdictions. A CCP should require participants to have sufficient financial resources and robust operational capacity to meet obligations arising from participation in the CCP.